Late Pleistocene and Holocene pollen stratigraphy at Lago di Vico, central Italy - Magri, Donatella; Sadori, Laura (Vegetation history and archaeobotany, 1999)
A new pollen record from Lago di Vico (core V1) provides fundamental new information towards re- construction of flora and vegetation history in central Italy during the last 90 000 years. The chronological framework is secured by seventeen AMS 14C dates, one 4°Ar/39Ar date and tephra analyses. At the base of the pol- len record, i.e. shortly after the 4°Ar/39Ar date 87 000+ 7000 B.P., three phases with significant expansion of trees are recorded in close succession. These forest phases, which stratigraphically correspond to St Ger- main II (and Ognon?) and precede pleniglacial steppe vegetation, are designated by the local names Etruria I, Etruria II and Etruria III. During the pleniglacial, a number of fluctuations of angiosperm mesophilous trees suggest the presence of tree refugia in the area. The low- est pollen concentration values are recorded at ca. 22 000 B.P. which corresponds with other pollen records from the region. The late-glacial is characterized by an expansion in the arboreal pollen curves that is less pro- nounced, however, than in other pollen profiles from Italy. The Holocene part of the profile is consistently dominated by deciduous oak pollen. No major changes in arboreal pollen composition are recorded but several marked and sudden declines of the tree pollen concentra- tion suggest that the forest cover underwent dramatic changes. Clear evidence for human impact is recorded only when cultivated crops became important which dates to ca. 26304-95 B.P.
Keywords: Central Italy; Crater lake; Holocene; Late Pleistocene; Pollen analysis